Strategi Digital Marketing PT. Indosat Ooredoo Medan Dalam Meningkatkan Kepercayaan Pelanggan - Yudi Hamdani (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2019)
For the digital marketing is very important not only in terms of trade with, in it but information and social development is felt its impact for users of social media.So the digital world demanded the entire community to get access, consume digital technology to be kept abreast of developments and information. socialOne of the ads also post, ooredoo indosat which confers prizes, quiz a race, creativity that is competition and competition. social mediaAs a form of services available to the community to actively participate in paying attention to the social media  program made by indosat ooredoo. It is called research pt marketing digital strategy.Indosat ooredoo a in increase the confidence of customers.Results is getting good, seen from several the interviews done that very influential digital marketing on the trust of customers because if it is seen post attractive, competitions which confers prizes, so the customers have more confidence in indosat. Facilities indosat application myim3 also the most helpful and ease to access packages offered.Nelfon and internet facilities provided indosat also needs a days has helped in the communication.